Adenoviral transfer of human interleukin-10 gene in lethal pancreatitis - Chen, Zi-Qian (World J Gastroenterol, 2004)
AIM: To evaluate the therapeutic effect of adenoviral-vector-delivered human interleukin-10 (hIL-10) gene on severe acute pancreatitis (SAP) rats. METHODS: Healthy Sprague-Dawley (SD) rats were intraperitoneally injected with adenoviral IL-10 gene (AdvhIL-10), empty vector (Adv0) or PBS solution. Blood, liver, pancreas and lung were harvested on the second day to examine hIL-10 level by ELISA and serum amylase by enzymatic assay. A SAP model was induced by retrograde injection of sodium taurocholate through pancreatic duct. SAP rats were then administered with AdvhIL-10, Adv0 and PBS solution by a single intraperitoneal injection 20 min after SAP induction. In addition to serum amylase assay, levels of hIL-10 and tumor necrosis factor-α (TNF-α ) were detected by RT-PCR, ELISA and histological study. The mortality rate was studied and analyzed by Kaplan–Meier and log rank analysis. RESULTS: The levels of hIL-10 in the pancreas, liver and lung of healthy rats increased significantly after AdvhIL-10 injection (1.42 ng/g in liver, 0.91 ng/g in pancreas); while there was no significant change of hIL-10 in the other two control groups. The concentration of hIL-10 was increased significantly in the SAP rats after AdvhIL-10 injection (1.68 ng/g in liver, 1.12 ng/g in pancreas) compared to the other two SAP groups with blank vector or PBS treatment (P < 0.05). The serum amylase levels remained normal in the AdvhIL-10 transfected healthy rats. However, the serum amylase level was significantly elevated in the other two control SAP rats. In contrast, serum amylase was down-regulated in the AdvhIL-10 treated SAP groups. The TNF-α expression in the AdvhIL-10 treated SAP rats was significantly lower compared to the other two control SAP groups. The pathohistological changes in the AdvhIL-10 treated group were better than those in the other two control groups. Furthermore, the mortality of the AdvhIL-10 treated group was significantly reduced compared to the other two control groups (P < 0.05). CONCLUSION: Adenoviral hIL-10 gene can significantly attenuate the severity of SAP rats, and can be used in the treatment of acute inflammation process.